Towards a Global Partnership Network: Implications, Evolution and Prospects of China's Partnership Diplomacy - SHENGSONG YUE (The Copenhagen Journal of Asian Studies, 2019)
In the past 25 years, partnership diplomacy has gradually become an indispensable component in China's grand diplomacy strategy. Between 1993 and the end of 2017, China established more than 100 partnerships with the outside world. To better understand the evolution of China's strategy for diplomacy we need to know how these partnerships are formed and what motivates China to foster its partnership network. Although the importance of this strategy has been identified, the current literature does not yet include significant study of China's partnership network. This article attempts to fill this gap by assessing existing literature on partnership and government documents, interpreting the diversified labels and grades of partnerships, and analysing the network's evolution. It also attempts to estimate possible challenges facing China in the future expansion of its global partnership network. It argues that, although China intends to further extend its global influence and explore potential benefits through its partnerships, because of the challenges ahead its partnership network is still an aspiration rather than a realistic blueprint.